Identification of the Backsheet Type of Silicon Photovoltaic Modules from Encapsulant Fluorescence Images - Stroyuk, Oleksandr; Guettler, Cosima; Buerhop-Lutz, Claudia; Hauch, Jens; Peters, Ian Marius (ACS Applied Energy Materials, 2022)
Feasibility of the identification of backsheet (BS) composition of field-aged Si photovoltaic (PV) modules based on the analysis of characteristic patterns of UV-excited fluorescence (UVF) of ethylene vinyl acetate copolymer encapsulant is shown. The approach includes BS identification by vibrational spectroscopies and the formation of a database of BS-related characteristic UVF patterns. A multivariate principal component analysis of the UVF images of unknown samples combined with the UVF pattern database allows the BS type to be identified only from UVF images. The geometric place of particular samples in the principal component plots is indicative of the general degradation status of PV modules. The proposed method can be applied for high-throughput noncontact characterization of solar PV plants.
CRIS-Team Scopus Importer:2023-03-07
Keywords: bill of materials; ethylene vinyl acetate copolymer; fluorescence imaging; photovoltaic modules; polymer degradation; PV encapsulants